Koch Fractal Loop Circular Polarization (CP) Antenna Integrated with Solar Cells - Alobaidi, O.R. (2020)
Minimal profile antennas for wireless devices which characteristics consisted of being low cost, highly reliable, and lightweight, it bears a new challenge for the design of the antenna in wireless communications. In this paper, we propose a design of circularly polarized microstrip patch antenna integration with solar cells for green wireless applications. Two techniques have been proposed to form the prototype between the communication system (design of antenna) and solar panel (solar cell). Both methods will face two issues generally; the solar system needs to get 100% sunlight and the magnetic field produced by radio communication systems as well as the electric field produced by solar cells should not affect the efficiency. The antenna is composed of a Koch fractal loop patch and the substrate is employed using a transparent material. This enables the light to pass through with high efficiency to illuminate the solar panel cells while the RF performance is maintained with minimal degradation. The communication frequency measures 2.6, 3.5 and 4.4 GHz. CST MWS simulation is also studied and compared among the different substrates which show different results based on the same parameters, which is implemented with a lattice of 2×2 square solar cells. With this arrangement, the solar cells will be able to obtain 100% of sunlight exposure. The characteristics of the broadband are achieved by combining resonances and the minimum axial ratio points created by the driven patch and solar cell surface. © 2019 IEEE.